Impact of the initiation of isCGM soon after type 1 diabetes mellitus diagnosis in adults on glycemic indices and fear of hypoglycemia: a randomized controlled trial - Hohendorff, Jerzy; Grzelka-Wozniak, Agata; Wrobel, Marta; Kania, Michal; Lapinska, Lidia; Rokicka, Dominika; Stoltny, Dorota; Kowalska, Irina; Strojek, Krzysztof; Zozulinska-Ziolkiewicz, Dorota; Malecki, Maciej T. (Frontiers in Endocrinology, 2025)
BackgroundContinuous glucose monitoring (CGM) improves glycemic control and quality of life. Data on glycemic indices and fear of hypoglycemia (FoH) in newly diagnosed T1DM patients are limited.AimTo assess the impact of initiating intermittently scanned CGM (isCGM) within 1–6 months of diagnosis on glycemic control and FoH in adults with T1DM.Subjects and methodsAfter wearing a blinded sensor for 14 days, participants were randomized (1:1) to either isCGM (intervention) or self-monitoring blood glucose (SMBG) with glucometers and blinded CGM (control). Primary outcomes were changes in time below 70 mg/dl (TB70) and FoH, assessed in the Hypoglycemia Fear Survey (HFS). Main secondary outcomes included changes in mean glucose and time in range (TIR) from baseline to 4 weeks after randomization.ResultsThe full analysis set included 23 patients (12 from the intervention group and 11 from the control group), aged 25.6 ± 5.1 years (14 men, 9 women). All participants were on multiple daily insulin injections. TB70 changed from 2.42% to 2.25% in the intervention, and from 2.81% to 1.82% in the control group, and the between-therapy difference of 0.83% was insignificant. No difference between intervention and control groups in change in HFS-worry and HFS-behavior subscales between baseline and after 4 weeks was found (−1.6 ± 3.2 and 1.0 ± 2.2, respectively). The mean glucose levels changed from 7.03 mmol/l to 6.73 mmol/l and from 7.07 mmol/l to 7.43 mmol/l, in the intervention and control groups, respectively, which resulted in a between-therapy significant glucose difference of −0.66 mmol/l. The mean TIR changed from 88.0% to 90.0% in the intervention group and from 85.2 to 84.1% in the control group—the between-therapy difference was insignificant (3,1%). The study ended early due to CGM reimbursement policy changes, after which most patients eligible for the study could have isCGM reimbursed.ConclusionsIn newly diagnosed T1DM adults, TIR is high and hypoglycemia risk is low. The study group was small; however, the data suggest that the use of isCGM soon after T1DM diagnosis could result in mean glucose decrease, but not in change in TB70 and FoH.